Study of structural, dielectric and AC conductivity properties of SrMoO4. (February 2022) - Thirmal, C.; Ramarao, S.D.; Rao, L. Srinivasa; Murthy, V.R.K.
Highlights: Polycrystalline SrMoO4 compound synthesized using conventional solid-state route. A frequency-dependent dielectric relaxation is observed near 795 K. Non-Debye type of relaxation in SrMoO4 is confirmed with the help of Nyquist plot. The SrMoO4 sample shows the negative temperature coefficient of resistance. The observed activation energies are correlated with motion of oxygen vacancies. Abstract: Strontium molybdate (SrMoO4 ) compound is synthesized using a solid-state reaction route. SrMoO4 was observed to form in tetragonal Scheelite structure with I 41 / a space group and is confirmed with the help of powder X-ray diffraction studies. The temperature-dependent dielectric constant measured at different frequencies indicated a maximum at around 795 K. The frequency-dependent dielectric maximum reveals the presence of a dielectric relaxation near 795 K. Further, the Nyquist plot analysis shows a depressed semi-circle and manifest the non-Debye type dielectric relaxation in SrMoO4 . The SrMoO4 compound possesses a negative temperature coefficient of resistance and is confirmed by fitting the Nyquist plot with a suitable equivalent circuit. The AC conductivity studies ascertain that the observed conduction mechanism in the SrMoO4 as a translational type correlated barrier hopping. The temperature-dependent AC conductivity reveals that the obtained activation energies are comparable with the oxygen vacancies and are responsible for observed dielectric relaxation. Graphical abstract: SrMoO4 ceramic compound showed an anomaly in the Differential scanning calorimetry data which further verified with the help of temperature-dependent dielectric measurements. Image, graphical abstract